1989
DOI: 10.1083/jcb.109.4.1519
|View full text |Cite
|
Sign up to set email alerts
|

Plasma membrane association of Acanthamoeba myosin I.

Abstract: Abstract. Myosin I accounted for "~2 96 of the protein of highly purified plasma membranes, which represents about a tenfold enrichment over its concentration in the total cell homogenate. This localization is consistent with immunofluorescence analysis of cells that shows myosin I at or near the plasma membrane as well as diffusely distributed in the cytoplasm with no apparent association with cytoplasmic organelles or vesicles identifiable at the level of light microscopy. Myosin II was not detected in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
81
0

Year Published

1989
1989
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(90 citation statements)
references
References 42 publications
9
81
0
Order By: Relevance
“…A mammalian myosin I has been localized to filopodia, lumellipodia, and fine punctae in the perinuclear region (61). In accordance with the in situ localization at membranes, in vitro biochemical experiments demonstrated a high affinity interaction of Acanthamoeba myosin rs and brush border myosin I with anionic phospholipids and membrane preparations (1,2,29,47).…”
supporting
confidence: 53%
“…A mammalian myosin I has been localized to filopodia, lumellipodia, and fine punctae in the perinuclear region (61). In accordance with the in situ localization at membranes, in vitro biochemical experiments demonstrated a high affinity interaction of Acanthamoeba myosin rs and brush border myosin I with anionic phospholipids and membrane preparations (1,2,29,47).…”
supporting
confidence: 53%
“…Because of its association with membranes in a number of diverse systems [Gadasi and Korn, 1980;Hagen et al, 1986;Miyata et al, 1989;Matsudaira and Burgess, 1979;Fukui et al, 1989;Adams and Pollard, 1989b], it has been suggested that myosin I functions as a mechanoenzyme in both organelle amoebae form lateral pseudopodia roughly three times as frequently as AX3 amoebae, and turn more often, presumably a result of the increased frequency of lateral pseudopod extension. Populations of DMIB-amoebae translocating in buffered salts solution exhibit many boomerang-shaped cells, suggesting frequent turning into lateral pseudopodia.…”
Section: Discussionmentioning
confidence: 99%
“…Some stretches have a high propensity to form a coiled-coil, which is proposed to induce the formation of dimers. In myosin Is, the tail homology I (TH1) domains were shown to have high-affinity phospholipid-binding sites (54,55), whereas the TH2 domains possess ATP-independent actin binding sites (56,57). A domain found in the tail of myosin VII and X has high homology to the membrane-binding domain of the talin/Band-4.1 family proteins.…”
Section: Myosins Are Tripartite Modular Motorsmentioning
confidence: 99%
“…The tail domains of the amoeboid myosins are generally composed of three subregions sometime referred to as TH1 to TH3 (tail homology domains 1 to 3). TH1 encompasses a stretch of polybasic residues implicated in high affinity phospho- (54,55). The amino acid composition of TH2 (also called GPA or GPQ) is highly biased towards Gly, Pro, and basic residues such as Lys (in myoC) or Arg, as well as to a lesser degree towards Ala (in myoC and myoD) or Gin (myoB).…”
Section: Structure/function Analysismentioning
confidence: 99%